1998
DOI: 10.5980/jpnjurol1989.89.657
|View full text |Cite
|
Sign up to set email alerts
|

Combination Chemotherapy With Cis-Platinum and Ifosfamide for Hormone Unresponsive Prostate Cancer

Abstract: We conclude that CDDP and IFM combination chemotherapy was active regimen for hormone unresponsive prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although myelosuppression was moderate to severe, no CT-related deaths or sepsis occurred, nor was there any clinical cardiotoxicity. In another study, performed by Maki et al [50], cisplatin/ifosfamide combination therapy was found to be an active regimen in patients with HRPC. Second-generation analogs of cisplatin have been produced which, in early studies, have had quantitatively less toxicity than the parent compound while retaining antitumor activity.…”
Section: Platinum Compoundsmentioning
confidence: 99%
“…Although myelosuppression was moderate to severe, no CT-related deaths or sepsis occurred, nor was there any clinical cardiotoxicity. In another study, performed by Maki et al [50], cisplatin/ifosfamide combination therapy was found to be an active regimen in patients with HRPC. Second-generation analogs of cisplatin have been produced which, in early studies, have had quantitatively less toxicity than the parent compound while retaining antitumor activity.…”
Section: Platinum Compoundsmentioning
confidence: 99%
“…In phase II trials, available cytotoxic drugs (e.g., alkylating agents, anthracyclines, antimetabolites, microtubular inhibitors and Pt-complexes) showed only moderate effects on the hormone refractory PC, with response rates between 27 and 41% (Raghavan et al 1997;Murphy 1999). The combinations of these drugs proved to be more active than their single components, but an extension of the survival time remains to be demonstrated (Maki et al 1998;Huan et al 1999;Gilligan and Kantoff 2002). Recently, attention was drawn to the benefit of satraplatin , an orally administrable Pt-complex, in the treatment of hormone refractory PC (Sternberg 2003).…”
mentioning
confidence: 99%